Review Of Siddha Drugs Are Used In The Treatment Of Kapalakarapan In Pararajasekaram Siroraganithanam - Thayalini, T.; Janshe, S.; Rakulini, R. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2017)
Pararajasekaram Siroroganithanam is a classic book written in a poetic form. It mentions diseases and their treatments related with neck and above. According to the mode of application, Siddha medicines are categorized into two classes. They are Internal medicine & external medicine. Medicinal plants are used to prepare medicines from ancient times for the treatment of various diseases in human beings. KapalaKarapan is a disease affects the scalp of the Head. Itching of the head, loss of hair, wounds with discharge on the scalp and lymph node enlargement are the clinical features of KapalaKarapan. Environmental changes, certain foods and infections are the causes of KapalaKarapan. Many drugs are mentioned for the KapalaKarapan in the Pararajasekaramsiroroganithanam. The aim of the study is to identify the types of Siddha drugs and its ingredients. Data were collected, tabulated and analyzed. Twenty drugs were identified from the analysis. Out of 20 drugs, 9 drugs (45%) are External application, 4 drugs (20%) are internal and 7 drugs (35%) are internal as well as external application. Among the 9 external medicine, 5(56%) are oil, 2 (22%) are poochchu, 1(11%) is fume as pukai, 1(11%) is kulambu. Four internal medicines are oil, katpam, kudineer and Chooranum.186 ingredients were identified from 20 medicines. Out of 186 ingredients, 171(92%) are herbs, 15(8%) minerals and metals. Among the 20 drugs, 10(50%) drugs contain Azimatetracanthaas one ingredient, over 40% of drugs contain Nigella sativa, Piper longum, Eclipta prostate, Acorus calamus and Zingeber officinalae.58% of Caster oil are used as base oil in the oils used in the treatment of Kapalakarapan. Previous researches showed that the above mentioned ingredients contain antimicrobial activity. Castor oil has purgative property used in the treatment of skin diseases including Karapan. Hence these drugs could be used in the Treatment of Kapalakarapan
Keywords: Drugs; Kapalakarapan; Review; Pararajasekaram